Development of a Kinetic Model for Low Temperature Fischer-Tropsch Synthesis - Davies, Imaad (Department of Chemical Engineering, 2021)
Globally, there is a need to replace our dependence on fossil fuels as the main source of energy. This requires a shift towards renewable and sustainable alternatives. The well-established FischerTropsch (FT) synthesis is a potential process route to produce liquid fuels and speciality chemicals and address this challenge. FT synthesis is a polymerisation reaction in which syngas, a mixture of CO and H2, is converted to hydrocarbon products ranging from methane to wax when low temperature conditions are used. Subsequent product upgrading steps allow high quality liquid fuels to be obtained which are clean burning. This will help to mitigate the impact of human activity on the environment. The versatility of this process route is attributed to the ability of syngas to be generated from any carbon-containing feed such as coal, natural gas or biomass. The latter is attractive to enable a shift to a more sustainable way of living. Particularly for biomass-to-liquid plants, the high cost of syngas generation means that FT synthesis should use syngas as efficiently as possible. This requires an effective description of the FT reaction kinetics. This study therefore focuses on the development of a kinetic model for low temperature FT (LTFT) synthesis to improve understanding of the reaction behaviour and aid in the development of a biomass-to-liquid process route. Although the kinetics of the FT reactions under the low temperature conditions of 180-260 ◦C and 20-30 bar(a) have been extensively studied, the challenge to kinetic model development is the large number of possible reaction products. A common simplification is to consider the formation of the main products only, which are linear n-paraffins and 1-olefins. The polymerisation character of FT synthesis means that its product distribution could ideally be described using models based on probability theory. Deviations from probability theory distribution, however, occur especially at the conditions of LTFT synthesis. These deviations are a high methane yield, low ethene yield and the change from mainly 1-olefins at low carbon number to mainly n-paraffins at high carbon number. Comprehensive kinetic models in literature focus on finding a kinetic explanation for these deviations. These kinetic models, however, cannot easily be used with few being extended to include the formation of products of higher carbon number. An aspect ignored in current kinetic model development is that FT synthesis shares many aspects of an equilibrium-controlled process. This is since CO hydrogenation which leads to monomer formation is the rate-determining step for the FT reactions. Consequently, the rate of chain growth is rapid in comparison. This leads to the distribution of n-paraffins and 1-olefins being controlled by equilibrium. By modelling FT synthesis as an equilibrium-controlled process, the kinetic model formulation could be simplified, consist of fewer rate expressions and contain the minimum number of model parameters without compromising on prediction quality. At the conditions of LTFT synthesis, both the vapour and liquid phases exist during reaction. The formation of liquid and its effect on the kinetics of FT synthesis has, however, often been neglected with most kinetic models considering the vapour phase only. This is despite of the effect that liquid formation has on product selectivity. The kinetic model developed in this thesis therefore aimed to combine the interaction between chemical equilibrium, kinetics and liquid formation and account for the formation of products of high carbon number. This will assist in providing a comprehensive description of the observed FT reaction behaviour in a simple and tractable manner. A pre-requisite to kinetic model development is the creation of a physical property database for nparaffins and 1-olefins which is extendable to high carbon numbers. This is since only the physical properties of low carbon number n-paraffins and 1-olefins are known because they are common in most industrial processes. For chemical and phase equilibrium calculations, the critical and ideal gas properties needed to be estimated. The Constantinou Gani group contribution method, with modification to the group contributions, proved to be an effective strategy to predict the physical property data for low carbon number n-paraffins and 1-olefins. The correlations developed should therefore provide an adequate approximation of the properties of their higher carbon number relatives. To model the phase behaviour of FT synthesis, the Peng-Robinson equation of state is used. Modifications were made to the alpha function of this equation of state to ensure it remained valid when the describing the behaviour of heavy hydrocarbons. The kinetic model development which relies on the equilibrium aspects of the reactions involved to describe the formation of n-paraffins and 1-olefins. The reaction pathway implemented is based on the alkyl mechanism and assumes that FT synthesis can be viewed as a methylene (CH2) polymerisation. In addition, the water gas shift (WGS) reaction is also considered. Methylene is taken as the monomer and enabled the reactions in FT synthesis to be represented using an equilibrium approach. Each rate expression is formulated as an equilibrium-controlled process, using species activity as the kinetic driving force. This proved to be an effective strategy to account for the observed reaction behaviour, namely a high methane yield, low ethene yield and the change from mainly 1-olefins at low carbon number to mainly n-paraffins at higher carbon number. This approach also allowed the model to effectively capture changes in product selectivity and the product distribution as a function of process conditions (CO conversion, temperature, pressure and H2/CO feed ratio). These changes could be explained by considering the equilibrium aspects of the reactions involved. The model only requires six adjustable parameters i.e. rate constants. An important part of model development is knowing how the model rate constants determine the model output. This provides insight regarding which rate constants can be determined from the regression of data. For this purpose, a sensitivity analysis was performed on the selectivity to C1, C2, C3, C4, C5+ and CO2 as a function of CO conversion. This analysis revealed that CO hydrogenation is rate-determining which agrees with findings in literature. This analysis also revealed that model rate constants are cross-correlated when product selectivity as a function of CO conversion data is studied. This means that meaningful estimation of all rate constants using data of this form is not possible. However, it was found that when product distribution data at constant CO conversion is used instead, then meaningful estimates of the rate constants could be determined. This is if CO conversion is below 60%. Over this CO conversion range, the product distribution is independent of the WGS reaction. The WGS rate constant should thus be approximated using data in literature. As such, five rate constants need to be determined from the regression of product distribution data. Model validation occurred by regression of product distribution data at constant CO conversion. Emphasis was placed on the ability of the model to predict changes in the product distribution with temperature. A quantitative measure of the model fit is the precision with which the rate constants were estimated. A good fit to experimental product distributions in both fixed-bed and slurry reactors is obtained. The kinetic model has therefore been shown to be independent of reactor type. The good fit to data is quantified by the small error in the estimated rate constants, particularly for CO conversions up to approximately 30%. Higher variability in the estimated rate constants was obtained for higher CO conversions. This emphasised the importance of estimating rate constants at conditions where the product distribution is most sensitive. The temperaturedependence of the rate constant could be described by an Arrhenius expression. The effect of liquid formation on the kinetic behaviour of FT synthesis was modelled by assuming that the vapour and liquid phases are in equilibrium. The choice of species activity as the kinetic driving force allowed the kinetic model to be applied in both the vapour and liquid phases. Although the system was mainly in the vapour phase, liquid formation alters selectivity. Single-phase simulations are valid up to a CO conversion of 20% and predict a higher selectivity to products of carbon number in the diesel product grade (C10-C20). Between a CO conversion of 20-90%, it becomes essential to account for liquid formation to ensure that the favourable selectivity to wax products (C21+) in FT synthesis is adequately captured. The predictions of the single- and two-phase simulations were assessed by comparison to the wax product from LTFT reactors in Sasol processes. Both simulations were found to be useful in describing these wax product distributions. The kinetic model developed in this thesis therefore effectively describes the behaviour of FT synthesis. The ability of the model to predict changes in product selectivity and the product distribution as a function of process conditions will make it a powerful tool involved in the design of FT processes. It is recommended that the approach taken to develop the model be used to study the kinetics of other gas-to-liquid processes, for reactor design and flowsheet development.